Women’s Resistance and Identity in the Kretek Industry through Kretek Girl : Resistensi dan Identitas Perempuan dalam Industri Kretek melalui Kretek Girl - Sari, Dea Puspita; Febriana, Poppy (House of Wisdom: Journal on Library and Information Sciences, 2025)
This Film is a mass media that can influence our views and beliefs, by combining audio and visual elements to convey the messages contained therein. The presence of women in the media industry is an interesting study to follow. The movie “Gadis Kretek” contains the movement of women's struggle in the kretek industry, highlighting the issue of gender inequality that is still influenced by patriarchal ideology. This research uses John Fiske's semiotic analysis method to understand the representation of women in the film, focusing on three levels: reality, representation, and ideology. The conclusion of this research shows the struggle in facing patriarchal inequality and domination in the movie “Gadis Kretek”. Inequality in the film Gadis Kretek can be seen from the limited role and space for women when managing the kretek industry and decision-making dominated by men so that patriarchal ideology emerges regarding the importance of women's awareness and empowerment in achieving their dreams in the kretek industry. Highlights: Limited Roles: Women are shown with restricted roles in the kretek industry. Patriarchal Dominance: Key decisions are controlled by men, reflecting patriarchal ideology. Women’s Struggle: The film highlights women’s fight against gender inequality. Keywords: Film, Representation, Semiotics, Women